OPTIMALISASI INTEGRAL FIN TUBE PADA SISTEM KONDENSASI LUAR BERDASARKAN FLOODING ANGLE : OPTIMALIZATION OF INTEGRAL FIN TUBE IN OUTSIDE CONDENSATION BASED ON FLOODING ANGLE - Khalida, Zulfa; Candra Dewi, Kartika; Musyarrofah, Siti; Rahmad, hadi; Puspa, Yulia (Jurnal Teknik Mesin, 2023)
Increasing heat transfer in condensation for low surface tension fluid is dominated by using extended area (fin). One of the extended area on pipe is integral fin tube. Designing of integral fin tube should be conducted due to generate optimal condition such as designing fin spacing. Fin spacing has significantly impacted to heat transfer enhancement. Whereas the material of pipe is copper since has higher heat conductivity than others and fluid working is methanol. To predict optimal geometry of integral fin tube is conducted by using mathematical simulation by dividing area into flooded and unflooded. The active area or unflooded area represents the heat transfer area adn enhancement. In this experiment is found that the optimum fin spasing is 1 mm